Hydraulic Strategy of Cactus Trichome for Absorption and Storage of Water under Arid Environment - Kim, Kiwoong; Kim, Hyejeong; Ho Park, Sung; Joon Lee, Sang (Frontiers in Plant Science, 2017)
Being an essential component in various metabolic activities, water is important for the survival of plants and animals. Cacti grown in arid areas have developed intrinsic water management systems, such as water collection through spines, water absorption through trichome, and water storage using mucilage. The water collection method of cactus is well documented, but its water absorption and storage strategies remain to be elucidated. Thus, this study analyzed the morphology and wettability of cactus trichomes by using advanced bio-imaging techniques and by performing experiments on an artificial system mimicking these structures, respectively. In addition, the in situ water absorption process through the trichome cluster was quantitatively visualized. This paper proposes a new bio-inspired technique for dew collection based on information about the water management strategies of cactus. This study discusses the underlying water absorption and storage strategies of cactus and provides the experimental database required to develop a biomimetic water management device.